ANALISIS SWOT DALAM MENENTUKAN STRATEGI PEMASARAN KEDAI WARUNG KOPI 777 SURABAYA - Rizka Novianty Haninda; Novita Dwi Indriyani; Izzah Mufidah Qurratu’ain (Yos Soedarso Economic Journal (YEJ), 2022)
The purpose of this study is to determine the right marketing strategy for businesses at Kedai Warung Kopi 777 Surabaya through a SWOT analysis. Therefore, the authors are interested in conducting research with the formulation of the problem. First, how is the marketing strategy for the business at the 777 Coffee Shop Surabaya. Second, how is the SWOT analysis in determining the right marketing strategy for the Kedai Warung Kopi 777 Surabaya business. This research is a field research with qualitative research type. To analyze the data using the IFAS, EFAS, SWOT matrix. The results of this study conclude that Kedai Warung Kopi 777 in terms of product, price, procces, place, promotion and people, phisycal eviden Kedai Warung Kopi 777 has implemented a strategy that is right on target with the company's goals. However, the physical evidence of Kedai Warung Kopi 777 did the wrong strategy so it needed to be evaluated. The strategy that can be used is the Kedai Warung Kopi 777 Surabaya based on the SWOT matrix, namely by maximizing promotions in online or offline media, prioritizing consumer satisfaction with product quality and affordable prices. Keywords: Marketing Strategy; SWOT Analysis.